Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

How to prove that the Laplace transform of $x^a$ is: $$\mathcal{L}\{x^a\}(s)=\frac{\Gamma(a+1)}{ s^{a+1}}$$ Also how to prove that the inverse Laplace transform of $\frac{\Gamma(a+1)}{ s^{a+1}}$ is $x^a$? Thanks a lot!!!

share|improve this question
    
By inverse function do you mean the inverse Laplace transform? –  Dennis Gulko Dec 17 '12 at 18:59
    
yes, inverse Laplace transform function; thanks for help me edit it in Latex : ) –  user53344 Dec 17 '12 at 19:00
1  
The standard way of proving that the inverse Laplace transform of $X$ is $Y$ is to prove that the Laplace transform of $Y$ is $X$. (Most authors just say "it's complicated" and brush it under the furniture when asked how to calculate inverse Laplace transforms.) –  Mario Carneiro Dec 17 '12 at 19:05

4 Answers 4

up vote 2 down vote accepted

By definition, the Laplace transform $\mathcal{L}(x^a)$ of the function $x\mapsto x^a$ is given by $$ \mathcal{L}(x^a)(s) = \int_0^\infty \exp(-sx)x^a\mathrm{d}x. $$

The Gamma function is defind by a similar integral, namely $$ \Gamma(s)=\int_0^\infty \exp(-x)x^{s-1}\mathrm{d}x. $$

The Laplace transform of $x^a$ can thus be computed by the variable transformation $x\mapsto x/s$.

share|improve this answer
    
then for the inverse function, I was wondering how to prove integral of (1/2pi*i)e^ptL(p) = x^a –  user53344 Dec 17 '12 at 19:18

You should use the definition of Laplace transform and of the Gamma function: $$\mathcal{L}\{f(x)\}(s)=\int_0^\infty e^{-sx}f(x)dx,\hspace{10pt} \Gamma(\alpha)=\int_0^\infty e^{-t}t^{\alpha-1}dt$$ Just substitute $f(x)=x^a$ and change the variable $sx\mapsto t$.

share|improve this answer

Use the definition of laplace transform ie. in your case , $$F(s) = \int_0^\infty x^a e^{-sx} dx$$

share|improve this answer

\begin{align*} \mathcal L\left\{ x^{a}\right\}&=\int\limits_0^\infty x^{a}e^{-{s}x}\text dx \\\text{let } x=\frac u{s}\qquad\quad\text dx=\frac{\text du}{s}& \\x=0\rightarrow u=0\qquad x=\infty\rightarrow u=\infty&\\ \\&=\int\limits_0^\infty \left(\frac u{s}\right)^{a}e^{-{s}\frac u{s}}\frac{\text du}{s} \\&=\frac{1}{{s}^{{a}+1}}\int\limits_0^\infty u^{a}e^{-u} {\text du}\\ \\&=\frac{\Gamma({a}+1)}{{s}^{{a}+1}}\\ \\&\color{grey}{=\frac{{a}!}{{s}^{{a}+1}},}&\qquad \color{grey}{{a}\in\mathbb Z\geq0} \end{align*}


\begin{align*} \mathcal L\left\{ x^{a}\right\}=\frac{\Gamma({a}+1)}{{s}^{{a}+1}}\\ \mathcal L^{-1}\Big\{\mathcal L\left\{ x^{a}\right\}\Big\}=\mathcal L^{-1}\left\{\frac{\Gamma({a}+1)}{{s}^{{a}+1}}\right\}\\ x^{a}=\mathcal L^{-1}\left\{\frac{\Gamma({a}+1)}{{s}^{{a}+1}}\right\}\\ \end{align*}

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.